A STANDARDIZED TRIPLE THERAPY COMBINED WITH ELECTRONIC MONITORING OF ADHERENCE NORMALIZES 24 H ABPM IN AT LEAST ONE THIRD OF PATIENTS WITH RESISTANT HYPERTENSION. (June 2018) - Wuerzner, G.; Berney, M.; Roduit, A. Planche; Schoenberger, R.; Ehret, G.; Pechère-Bertschi, A.; Burnier, M.
Abstract : Objective: Poor adherence to drug therapy is one of the most common factor explaining a poor blood pressures (BP) control in patients with apparent resistant hypertension. Few studies have used a standardized treatment coupled to electronic adherence monitoring in patients with apparent resistant hypertension. The objective of this study was to determine the rate of BP control when prescribing a standardized triple therapy associated with electronic monitoring of drug intake for 3 months and assessing BP control using 24 h ambulatory BP monitoring (ABPM). Design and method: Patients with 3 antihypertensive drugs and residual hypertension on 24 hr ABPM (excluding white coat hypertension) were recruited. A single pill combination of olmesartan 40 mg and amlodipine 10 mg was prescribed together with 25 mg chlorthalidone for 3 months. Medications were provided in 2 separated electronic pills boxes (MEMS®) recording the date and time of each opening. Patients were seen at 6 and 12 weeks. At 3 months, we analyzed MEMS® data and performed a second ABPM. Results: 49 patients (36% women) were included: 36 had complete data sets. Mean age was 56.5 ± 11.9 y, BMI was 31.2 ± 5.1 kg/m2. Overall, mean 24 h systolic BP (SBP) decreased from 148 ± 19 mmHg to 129 ± 16 mmHg (p < 0.001) and diastolic BP (DBP) decreased from 89.0 ± 16.1 mmHg to 77.5 ± 10.5 mmHg (p < 0.001). Overall 50 % of patients normalized SBP and 36% normalized both SBP and DBP. Median taking adherence (%) was respectively 92.5 % (interquartile range (IQR) 84.0–100) and 91.9 % (IQR 83.0–100) for the fixed combination and chlorthalidone. When analyzed according to tertiles of adherence, decreases in SBP were respectively 27 ± 16.6 mmHg in tertile 1 (99–100%), 20 ± 31 mmHg in tertile 2 (89–98.9%) and 9.1 ± 15.4 mmHg. in tertile 3 (0–88%) (p = 0.027 for trend). Conclusions: A simplified standardized antihypertensive therapy together with an electronic monitoring of adherence enables to normalize BP in more than 1/3 of patients with apparent resistant hypertension and no white coat effect. BP reduction correlates with the level of adherence. This diagnostic and supportive strategy may prevent from expensive and unnecessary investigations.